Impacto das culturas de cobertura de inverno e pré-emergentes na fitossociologia de plantas daninhas no sistema de produção de soja - Grün, Eduarda (2024)
Weed resistance to herbicides and the need for sustainable strategies to manage these species are central concerns in agriculture. In this sense, the objectives of this study were to evaluate the occurrence of weeds in soybean systems with different vegetation cover (article I), as well as to evaluate the effect of pre-emergent herbicides in different soybean cropping systems (article II). The studies related to article I were carried out in Júlio de Castilhos, Santa Maria, Capão do Leão, Barra do Ribeiro and Santo Ângelo, in Rio Grande do Sul, Brazil. The treatments consisted of black oat (Avena strigosa Schreb.), white oat (Avena sativa L.), rye (Secale cereale L.), vetch (Vicia sativa L.), forage radish (Raphanus sativus L.) and white clover (Trifolium repens L.) in pure crops or in mixtures. The variables analyzed were relative frequency, density, abundance, relative importance value index (IVIR), weed similarity index, dry mass of the plant cover and soybean yield. The plant covers containing white or black oat reduced the relative importance value index of weeds, such as Lolium multiforum, Conyza spp. and Bidens pilosa. Forage radish, vetch and white clover showed distinct responses. Black oat and forage radish did not differ from the cover mixtures in terms of dry mass and grain yield, being superior to fallow, white clover and vetch. The studies related to article II were conducted between 2020 and 2024 in Santo Ângelo and Santa Maria. In the municipality of Santo Ângelo, the experiments were conducted in a conventional cultivation system and in a no-tillage system, while in Santa Maria they were conducted in no-tillage. The treatments consisted of the following herbicides applied in pre-emergence, in the plant-and-apply modality: control without application; pyroxasulfone + flumioxazin; diclosulam; trifluralin; flumioxazin; sulfentrazone + diuron; s-metolachlor; chlorimuron-ethyl; sulfentrazone; imazethapyr; pendimethalin; imazethapyr + flumioxazin; metribuzin; s-metolachlor + fomesafen and; s-metolachlor + metribuzin. The IVIR, phytotoxicity, Simpson, Shannon-Wiener and similarity indices were evaluated at 25 and 40 days after emergence. Pyroxasulfone + flumioxazin, chlorimuron-ethyl, imazethapyr + flumioxazin, metribuzin, and s-metolachlor + fomesafen were effective in reducing the IVIR of Raphanus raphanistrum. Euphorbia heterophylla had the lowest IVIR observed in sulfentrazone and flumioxazin. Sulfentrazone + diuron, s-metolachlor and s-metolachlor + fomesafen showed phytotoxicity but did not negatively impact productivity. The integration of management practices, such as the adoption of plant covers and pre-emergent herbicides, was configured as a promising strategy for weed control in soybean crops. The importance of carefully selecting management practices is highlighted, aiming to reduce competition from weeds and maximize agricultural productivity.